T7 DNA polymerase treatment improves quantitative sequencing of both double-stranded and single-stranded DNA viruses - Billaud, Maud; Theodorou, Ilias; Lamy-Besnier, Quentin; Shah, Shiraz A.; Lecointe, François; De Sordi, Luisa; De Paepe, Marianne; Petit, Marie-Agnès (Peer Community Journal)

(untitled)
Bulk microbiome, as well as virome-enriched shotgun sequencing only reveals the double-stranded DNA (dsDNA) content of a given sample, unless specific treatments are applied. However, genomes of viruses often consist of a circular single-stranded DNA (ssDNA) molecule. Pre-treatment and amplification of DNA using the multiple displacement amplification (MDA) method enables conversion of ssDNA to dsDNA, but this process can lead to over-representation of these circular ssDNA genomes. A more recent alternative permits to bypass the amplification step, as library adapters are ligated to sheared and denatured DNA, after an end-modification step (xGen kit). However, the sonication step might shear ssDNA more efficiently than dsDNA, therefore introducing another bias in virome sequencing. These limitations prompted us to explore an alternative method of DNA preparation for sequencing mixed ssDNA and dsDNA viromes. Using a synthetic mix of viral particles, we made use of the T7 DNA polymerase (T7pol) to convert viral circular ssDNA molecules to dsDNA, while preventing over-replication of such molecules, as is the case with the Phi29 DNA polymerase. Our findings indicate that using  T7pol  and a mix of degenerated primers to convert ssDNA to dsDNA prior library preparation is a good alternative to the currently used methods. It better represents the original synthetic mixtures compared to MDA or direct application of the xGen kit. Furthermore, when applied to two complex virome samples, the T7pol treatment improved both the richness and abundance in the Microviridae fraction. We conclude that T7pol pretreatment is preferable to MDA for the shotgun sequencing of viromes, which is easy to implement and inexpensive.